2010
DOI: 10.1111/j.1442-2050.2009.00976.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical manifestation of esophageal carcinosarcoma: a Taiwan experience

Abstract: Carcinosarcoma of the esophagus is a rare neoplasm with both carcinomatous and sarcomatous components. This study aimed to investigate its clinicopathologic features and endoscopic characteristics. The data of patients diagnosed to have esophageal carcinosarcoma pathologically in the past 30 years (January 1976-December 2007) were reviewed. Of 3318 cases of esophageal malignancy, 12 were diagnosed as esophageal carcinosarcoma, with an incidence of 0.36%. All of the cases were male with a mean age of 62.3 years… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
24
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 23 publications
2
24
0
3
Order By: Relevance
“…In accordance with the previous reports, [1,11,19,20] most of the SpCC patients (67.6%) were in stage T1/2 at initial diagnosis, but only 29.7% for typical SCC were T1/2 ( P  < 0.001), suggesting that SpCC was more likely to be diagnosed at an early stage. However, as reported, [1,11,19] no significant difference was found in harboring lymph node metastasis between both the groups even at stage T1/2 (41.7% vs 37.1%). This indicates that SpCC tends not to infiltrate deeply into the esophageal wall, but it presents a highly aggressive tendency of lymphatic spread even at the early T stage.…”
Section: Discussionsupporting
confidence: 92%
“…In accordance with the previous reports, [1,11,19,20] most of the SpCC patients (67.6%) were in stage T1/2 at initial diagnosis, but only 29.7% for typical SCC were T1/2 ( P  < 0.001), suggesting that SpCC was more likely to be diagnosed at an early stage. However, as reported, [1,11,19] no significant difference was found in harboring lymph node metastasis between both the groups even at stage T1/2 (41.7% vs 37.1%). This indicates that SpCC tends not to infiltrate deeply into the esophageal wall, but it presents a highly aggressive tendency of lymphatic spread even at the early T stage.…”
Section: Discussionsupporting
confidence: 92%
“…6 In a study with Taiwanese patients, Kuo et al 7 reported that approximately 33% (4/12) of carcinosarcoma had previous head and neck squamous cell carcinoma that occurred metachronously. However, there has been no previous report on metachronous development of esophageal squamous cell carcinoma in a patient with carcinosarcoma.…”
Section: Discussionmentioning
confidence: 99%
“…Otras entidades tales como melanoma maligno y sarcomas como histiocitoma maligno fibroso completan la lista de diagnósticos diferenciales 5,6,7,8,9 .…”
Section: Discussionunclassified
“…Para grandes lesiones puede considerarse la quimiorradioterapia preoperatoria. Se han descrito también casos de carcinosarcoma a nivel gástrico, tal como inicialmente fue planteado en el caso presentado en este artículo 6,9,11,14 .…”
Section: Discussionunclassified
See 1 more Smart Citation